Analysis of Vegetables Marketing Strategy at Center of Agriculture Course and Self-Subsistent Rural Areas (P4S) Wanua Lampoko - Suherman Suherman; Asrijal Asrijal; Fitry Purnamasari; Sri Hardianti Rosadi (Agribusiness Journal, 2023)
One of the enormous potentials in the agricultural sector is horticulture, which plays an important role in ensuring adequate nutrition for the community such as vegetables, fruit, flowers, live plants, etc. Wanua Lampoko Independent Agricultural and Rural Training Center (P4S), Lampoko Village, Barebbo District, Bone Regency is an agricultural education and training institution which is a forum for education and teaching for farmers and agricultural practitioners as well as coaching farmers in the fields of agriculture, horticulture, animal husbandry, fisheries , plantations and other social fields that are just and sustainable. The aim of this research is to analyze the Vegetables Marketing Strategy at P4S Wanua Lampoko. The method used is SWOT analysis with stages, namely problem definition, data collection, data processing, data analysis and drawing conclusions. The results of the SWOT matrix show that from several IFAS internal factors and EFAS external factors, P4S has quite large strengths with a score of 1.971 which is higher than the weakness score of 1.536. However, there is a threat to the score1,882whose value is close to the strength score and greater than the opportunity score of 1.653. The position of P4S Wanua Lampoko is in quadrant II, which means that even though it faces various threats, P4S Wanua Lampoko still has strength from an internal company perspective. The strategy that must be established is to use strengths to take advantage of long-term opportunities with a diversification strategy. P4S Wanua Lampoko, which is based on the ST (Strength and Treats) strategy, is expected to be able to control product prices to increase people's purchasing power, use quality seeds to increase production and quality of vegetables sold.